The Association of SNPs Located in the CDKN2B-AS1 and LPA Genes With Carotid Artery Stenosis and Atherogenic Stroke - Lasek-Bal, Anetta; Kula, Dorota; Urbanek, Tomasz; Puz, Przemysław; Szymszal, Jan; Jarzab, Michał; Halczok, Monika; Cyplinska, Renata; Bal, Wiesław; Łabuz-Roszak, Beata; Cieślik, Aleksandra; Jasnos, Ilona; et al. (Frontiers in Neurology, 2019)
Introduction The aim of this project was to assess the prevalence of four selected SNPs rs4977574 and rs7857345 (CDKN2B-AS1 gene) and rs3798220 and rs10455872 polymorphisms (the LPA gene) in the subpopulation of patients with symptomatic and asymptomatic carotid stenosis. Material and Methods This study included 623 individuals (244 patients with symptomatic carotid artery stenosis, 176 patients with asymptomatic carotid artery stenosis and 203 healthy people. All the participants underwent neurological examination, duplex Doppler ultrasound examination and molecular procedures. Results In the first part of the analysis the assiociation of SNPs with stroke/TIA was investigated. The association was seen in symptomatic vs control group for two SNPs: rs4977574 and rs7857345 (CDKN2B-AS1 gene); genotype distributions for rs4977574 and rs7857345 showed the statistically significant differences between patients and controls (p=0.043 and 0.017, respectively). No association was observed for rs3798220 and rs10455872 located in the LPA gene. There were statistically significant differences between asymptomatic patients vs control group in genotype distribution for the SNPs located in CDKN2B-AS1: rs4977574 and rs7857345 (p=0.031 and 0.0099, respectively); and for the rs3798220 (LPA gene; p=0.003); however, statistically significant differences did not occur for the rs10455872 polymorphism located in the LPA gene. In the next part of the evaluation, a comparison between symptomatic and asymptomatic patients was performed. Significant differences in genotype distribution were seen only for the rs3798220 polymorphism located in the LPA gene (p=0.0015). The analysis of the prevalence of the polymorphisms in the total group (symptomatic and asymptomatic) patients in comparison with the control group showed significant differences for three polymorphisms: rs4977574 and rs7857345 (CDKN2B-AS1 gene; p=0.015 and 0.0046, respectively) and rs3798220 (LPA gene, p=0.044). Conclusions The present research on the carotid artery stenosis patient cohort suggests the significant association between the rs4977574, rs7857345 and rs3798220 polymorphisms and carotid artery stenosis as well as between the rs4977574 and rs7857345 polymorphisms and atherogenic stroke. The rs4977574 and rs7857345 polymorphisms in patients with carotid artery stenosis appear to affect a person's susceptibility to atherogenic brain ischemia. Our results need to be replicated in future studies.